Obesity negatively impacts outcome in elderly female patients with aggressive B‐cell lymphomas treated with R‐CHOP2: results from prospective trials of the German high grade non‐Hodgkin's lymphoma trial group. (28th November 2017) - Hohloch, K.; Altmann, B.; Pfreundschuh, M.; Loeffler, M.; Schmitz, N.; Zettl, F.; Ziepert, M.; Trümper, L.
Summary: To study if obesity is a risk factor in elderly patients (>60 years) with aggressive B‐cell lymphoma, the outcomes of 576 elderly patients treated with rituximab in the RICOVER‐60 trial were analysed in a retrospective study with regard to body mass index (BMI) and gender. Of the 576 patients, 1% had low body weight (BMI < 18·5), 38% were normal weight (18·5 ≤ BMI < 25), 42% were overweight (25 ≤ BMI < 30) and 19% were obese (BMI ≥ 30). Event‐free (EFS), progression‐free (PFS) and overall survival (OS) according to BMI showed no significant differences for all and for male patients. EFS ( P  = 0·041), PFS ( P  = 0·038) and OS ( P  = 0·031) were significantly better for female non‐obese patients. A multivariate analysis adjusted for International Prognostic Index risk factors confirmed these results, with the following hazard ratios (HR) for obesity (BMI ≥ 30) for EFS/PFS/OS: all patients – 1·4/1·4/1·4 (not significant); male patients – 1·2/1·2/1·0 (not significant) and female patients – 1·7 ( P  = 0·032)/1·9 ( P  = 0·022)/2·0 ( P  = 0·017). In conclusion, obesity is a risk factor that influences treatment outcome in elderly female patients with aggressive B‐cell lymphoma treated with R‐CHOP (rituximab + cyclophosphamide, doxorubicin, vincristine, prednisolone). The inferior outcomes in obese female patients may be due to faster rituximab clearance in obese females.